A micro-turbine-generator-construction-kit (MTG-c-kit) for small-scale waste heat recovery ORC-Plants. (15th August 2019) - Weiß, A.P.; Popp, T.; Zinn, G.; Preißinger, M.; Brüggemann, D.
Abstract: Experimentally determined efficiency characteristics of two micro turbines are discussed in this paper. One turbine (15 kW) is working with cyclopentane, the other turbine (12 kW) expands hexamethyldisiloxane (MM). The two turbines are designed and built in accordance to the concept of a micro-turbine-generator-construction-kit (MTG-c-kit) for small-scale Organic Rankine Cycle (ORC) waste heat recovery. The motivation for this MTG-c-kit and its architecture will be briefly introduced. Both single stage impulse turbines show a high design point total-to-static isentropic efficiency: the 15 kW cyclopentane turbine achieves 65.0%, the 12 kW hexamethylidisiloxane turbine achieves even 73.4%. Furthermore, the discussed off-design characteristics of the turbines prove that their operating behavior is very advantageous for small waste heat recovery plants - the turbine efficiency keeps a high level over a wide range of pressure ratio and rotational speed. Highlights: Introduction of a Micro-Turbine-Generator-Construction-Kit for ORC plants. Experimental results for two different representatives of this kit. Confirmation that the kit is practical for small-scale waste heat recovery. Proof that micro turbines are competitive as expander for ORC plants <100 kWel . Abstract.